A new species of Telmatobius (Anura, Ceratophryidae) from Northern Jujuy Province, Argentina - Barrionuevo, J. Sebastián; Baldo, Diego (Zootaxa, 2009)
We describe a new species of frog of the genus Telmatobius from Laguna de Los Pozuelos basin in the northernmost region of Argentina in Jujuy province. Osteological, larval and karyological characters are also included. Telmatobius rubigo sp. nov., was previously referred as T. marmoratus, from which is easily distinguishable by the coloration pattern of adults, metamorphs and tadpoles, and other morphological features. The new taxon is compared with the other species from Argentina and from the neighboring Andean regions of Bolivia and Chile.